2002
DOI: 10.1177/002246690203500404
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Video Instruction to Teach Persons with Moderate Intellectual Disabilities to Read Grocery Aisle Signs and Locate Items

Abstract: The purpose of this study was to evaluate the use of computer-based video instruction to teach generalized reading of words found on grocery store aisle signs and the location of the corresponding grocery items within those aisles. A multiple probe design across three sets of words, replicated across four students with moderate intellectual disabilities, was used to evaluate the effectiveness of the computer-based video program. All training sessions occurred through simulation using the computer-based program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(116 citation statements)
references
References 21 publications
13
100
0
3
Order By: Relevance
“…It also proved that students who use computer achieved higher marks than the students who follow the traditional methods of learning (Stromer et al, 1996;Yeuingoo Lee, 2001;Heimann et al, 2001;Mechling, Gast, & Langone, 2002;Aweys, 2007).…”
Section: Problem Statementmentioning
confidence: 97%
“…It also proved that students who use computer achieved higher marks than the students who follow the traditional methods of learning (Stromer et al, 1996;Yeuingoo Lee, 2001;Heimann et al, 2001;Mechling, Gast, & Langone, 2002;Aweys, 2007).…”
Section: Problem Statementmentioning
confidence: 97%
“…In addition, several studies have documented the application of systematic instruction as an evidence-based practice for teaching academic skills to children with disabilities (Morse & Schuster, 2004;Browder et al, 2009). In this systematic review, four studies applied systematic instruction as a strategy of teaching various academic skills to students with multiple disabilities (Jameson et al, 2007;Mechling, Gast, & Langone, 2002;Smith et al, 2011;Browder, Hudson & Wood, 2013). Jameson et al (2007) demonstrated that systematic instruction is also an evidence based practice where students are taught word and symbol recognition using differential reinforcement and constant time delay among students with moderate intellectual disabilities.…”
Section: First Research Questionmentioning
confidence: 99%
“…Jameson et al (2007) demonstrated that systematic instruction is also an evidence based practice where students are taught word and symbol recognition using differential reinforcement and constant time delay among students with moderate intellectual disabilities. Similarly, Mechling, Gast, and Langone (2002) successfully applied video simulations in teaching students who had moderate intellectual disabilities the task analysis steps for tracing items within a grocery store. Smith et al (2011) on the other hand applied simultaneous prompting in teaching food classification information and restaurant sight words to students with both severe and moderate intellectual disabilities.…”
Section: First Research Questionmentioning
confidence: 99%
“…There were studies investigating whether CAVI was effective in the field, and it was determined that Mechling was involved in most of these investigations. Mechling, Gast, and Langone (2002) conducted a survey of students with moderate intellectual disabilities who aimed to gain market share markings and to read their placements with CAVI. As a result, it has been found that CAVI is effective in enabling students to read signs indicating the location of the items in the grocery stores.…”
Section: Tartışma Ve Sonuçmentioning
confidence: 99%